The Implementation of Innovation Program Report: 3 in 1 Anion Bed Operating Pattern For Water Efficiency and Water Pollution Loads Improvement - SUSILO, Sofiyan Dwi; PRASETYO, Arif Eko; SETYAWAN, Wawan; ICHWAN, Munirul; INTAN, Indo; KARNYOTO, Andrea Stevens (International Journal of Environmental, Sustainability, and Social Science, 2024)
In Tuban Regency, East Java, Indonesia, PT PLN Nusantara Power Unit Tanjung Awar-Awar Power Plant was built. There are two 350 MW coal-fired plants in operation. This project was built based on Presidential Regulation of the Republic of Indonesia No 71 of 2006 dated July 5, 2006 concerning assignment to PT PLN. The company is committed to the environment. They hire a highly skilled team of technicians and engineers to run water treatment plants (WTP). The PT PLN Nusantara Power Unit Tanjung Awar-Awar was able to solve many problems that were caused by the WTP by analyzing data and observing actual conditions. Specially to address concerns such as efficiency, safety, and saving money. A challenge of WTP operation is the limited ability of ion exchange resin (Anion) to remove impure ions from raw water. Hence, PLN introduced an innovative program called "THE IMPLEMENTATION OF 3 IN 1 ANION OPERATION PATTERN". We developed this program because anion beds need to be replaced every so often. The program reduces anion bed component replacement frequency. Due to the WTP's two anion beds, this operating method is possible. The first three days of operation are spent using Anion Bed-A, while Anion Bed-B remains on standby. We're contributing to 1) the anion bed replacement has been cut from once a month to once every three months, 2) significant reductions in waste water pollution load in 2022 of TSS=0,000624 tonnes and CL=0.00000714 tonnes.